Distribution of concentration of impurities and "impurity–vacancy" complexes beyond the range of ions during implantation - V. I. Sugakov; A. A. Chernyuk; Institute for Nuclear Research, National Academy of Sciences of Ukraine, Kyiv, Ukraine (Ядерна фізика та енергетика)
Spatial distribution of implanted atoms and point defects created by irradiation is calculated beyond the range of ions in the crystal with impurities. Diffuse movement of defects and impurities, their capture by their effluents, the processes of recombination defects, formation and decay of complexes are taken into account. The crystal is considered at the temperature when impurities are still and impurity complexes with vacancies can move in the crystal. This situation is realized in silicon mixed with the oxygen. It is shown that the spatial redistribution of the concentrations of free impurities and impurities connected with vacancies is taking place beyond the range of ions: certain region at the end of ion range becomes impoverished in complexes and enriched in free impurities. This region increases with lowering the dislocations density or with decreasing temperature and can reach the size of several tens of micrometers.